Exploring the Potential of Two Bacterial Consortia to Degrade Cellulosic Biomass for Biotechnological Applications - Constancio, Milena Tavares Lima [UNESP]; Sacco, Laís Postai [UNESP]; Campanharo, João Carlos [UNESP]; Castellane, Tereza Cristina Luque [UNESP]; de Oliveira Souza, Anna Carolina [UNESP]; Weiss, Bruno [UNESP]; de Mello Varani, Alessandro [UNESP]; Alves, Lúcia Maria Carareto [UNESP] (Springer Nature, 2020)
This paper outlines two cellulolytic bacterial consortia named SCS and SCB, isolated from soil samples of sugarcane (Saccharum officinarum) crop field, and a sugarcane bagasse deposit in an ethanol mill. Both consortia were able to grow on different carbon sources, such as sugarcane bagasse, corn husk, peanut hulls, and carboxymethylcellulose, releasing up to 11.90 µmol/mL and 15.23 µmol/mL of glucose for SCS and SCB, respectively. In addition, SCS and SCB have several strains capable of producing cellulase, amylase, lipase, and protease. Whole genome sequencing of the SCS consortium revealed that Burkholderia was the most prevalent genus, encompassing approximately 80% of the consortia. In addition, metagenome analysis allowed the identification of genes encoding enzymes related to starch and cellulose degradation, as well as enzymes related to lipases and proteases, confirming our initial findings. The results showed that SCS and SCB had the capability to degrade cellulose, and that they were an efficient source of enzyme production, which would provide a new choice for use in different biotechnological applications.